Educação quilombola, resistência e empoderamento: estudo na comunidade quilombola de São Domingos em Paracatu - MG - Franco Gomes, Lara Luisa Silva (2018)
This dissertation was developed within scope Post-Graduation Program Education Federal University of Uberlandia, in the research line State, Policies and Education Management. It addresses the implementation curricular guidelines for Quilombola Education within the Quilombo São Domingos Community, Paracatu is a municipality in Minas Gerais, Brazil. It has as object analysis quilombola education in the Community São Domingos. Its main objective was understand how the public policies to Quilombola School Education within the São Domingos Community materialize. Question: who are responsible for the implementation of public policies for quilombola education in the São Domingos Community? The research is configured as ethnographic, therefore qualitative, used the techniques of bibliographic review, documentary analysis and action research. The methodological procedures were part of initial work researcher in the extension project called Interdisciplinary Experimentation in Quilombola Communities, developed by UFU in June 2016 and experience field until February 2017, which involved all the subjects Community, with two interviewees. The results highlight gaps between, legal consensus around racial issues and the materialization achievements in the context practice; shows some contradictions involved in the process construction quilombola identity, education and self-knowledge the community; points to the quilombola resistance for their rights for schooling, land, survival and for a better future; evidences the role oral history, culture and ancestry within community organization, as well as highlights some vacuums left by the absence of quilombola school education in that area and the silencing of quilombola culture in the school curricula schools that serve students the community, even with proactive advances legal slides. It concludes the importance of the University in fulfilling one goals university extension policy: to contribute to social justice in the country, in view the need to expand the rights of quilombola communities, such as quilombola school education. The relevance this research is contribution Brazilian black researchers in the interpretation social context Afro-Brazilians to implementation educational social policies.